TEACHERS’ PERCEPTIONS OF THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN PRIMARY SCHOOLS: A QUALITATIVE STUDY - Muhamad Ridwan (JURNAL ASIK, 2026)
This study explores primary school teachers’ perceptions of the implementation of the Independent Curriculum using a qualitative descriptive approach. The research was conducted in selected primary schools in Ciamis, Indonesia. Participants were purposively selected and consisted of teachers who had experience implementing the Independent Curriculum. Data were collected through semi-structured interviews and supported by observations and document analysis. Thematic analysis was employed to identify key patterns and meanings from participants’ experiences. The findings reveal that teachers generally hold positive perceptions of the Independent Curriculum, viewing it as a progressive reform that promotes instructional flexibility and student-centered learning. Teachers reported increased opportunities to address diverse student needs through project-based activities and formative assessment. However, significant challenges were also identified, particularly limited understanding of differentiated instruction, difficulties with authentic assessment, and increased administrative workload. These constraints often resulted in partial curriculum implementation. Institutional support emerged as a critical factor influencing teachers’ confidence and adaptability. Teachers who received continuous professional development and leadership support demonstrated greater readiness to apply innovative teaching strategies. In contrast, disparities in training opportunities and learning resources contributed to uneven implementation across schools. To address these challenges, teachers adopted adaptive strategies such as peer collaboration, joint lesson planning, and self-directed learning. The study concludes that while teachers largely embrace the philosophy of the Independent Curriculum, effective implementation requires sustained professional development, reduced administrative burden, equitable resource distribution, and strong school leadership. These findings highlight the importance of context-sensitive support systems to ensure meaningful curriculum transformation at the primary education level.